RESPOSTAS NEUROMUSCULARES E ANTROPOMÉTRICAS DE IDOSAS SUBMETIDAS A DOIS DIFERENTES TIPOS DE PERIODIZAÇÕES DO TREINAMENTO DE FORÇA. - SILVA, Surama do Carmo Souza da (2018)
Resistance training (RT) can induce increased strength even in the elderly women. However, the manipulation and organization of variables in training through periodization and its effects need further clarification. Thus, the objective of the present study is to evaluate the effects of linear periodization and daily undulatory periodization on neuromuscular and anthropometric functions in elderly women. Twenty-two elderly women (64 ± 3 years) was randomized into two experimental groups: linear periodization (LP, n = 12) and daily undulating periodization (DUP, n = 10). Was evaluated the anthropometry through weight, height, bioimpedance and perimetry; the submaximal force through the test of 10 maximal repetitions (10RM) in the horizontal leg press (HL), pulldown (PD), leg curl (LC), vertical bench press (BP) and leg extension (LE). A battery of functional tests was performed: Timed up & go (TUG), 30 second timed sit test (TST-30s), vertical jump test (VJ) and shuttle run (SR). Participants were submitted to RT 3 times a week (Monday, Wednesday and Friday) for 12 weeks. Data are presented as mean and standard deviation, and descriptive analysis. Initially, the Shapiro Wilk normality test and the Levene test were performed. To compare the initial characteristics of the sample and analysis of the delta variables, was used the Student t test. For comparison of pre and post-test was used the two-way ANOVA test (24-hours food recall (R24hs), temrepetition maximum testing (10RM), relative strength, functional tests, anthropometry and metabolic risk) with post hoc Tukey test (p <0.05). Effect size was also performed for strength (10RM and relative strength), functional, anthropometric and metabolic risk variables. Statistical analyzes was performed in the statistical package SPSS (version 18). The 10RM tests presented excellent reproducibility (ICC ≥ 0.75, p <0.01). Participants were initially classified as overweight or obese in BMI, with moderate to high risk in HWR, WC and WHR, and excessive or obese %F. Periodizations induced increased submaximal strength (10RM) and relative strength (body weight and lean body mass), improvement in functional capacity, but no change in anthropometry (except arm relax, p = 0.000) and metabolic risk. The Effect Size classified the changes in relative strength / lean mass (both groups) and leg press (for the PL group) as high effect, and relative strength / body mass as medium or small effect for both groups. Regarding the functional tests, the TUG and TST tests had a high effect for the POD group. The other variables had a trivial or small effect. It was concluded that both periodizations were able to increase submaximal muscle strength and relative strength, and to improve functional capacity after 12 weeks of TF, but with little effect on anthropometry and metabolic risk in elderly women. There were no significant differences between periodizations.